Demonstratives in Nivkh: A Semantic and Pragmatic Analysis - Ekaterina Gruzdeva (Studia Orientalia Electronica, 2020)
This paper offers a comprehensive analysis of the morphosyntactic, semantic and pragmatic features of Nivkh demonstratives, which represent a typologically interesting example of an exceptionally elaborated speaker-anchored deictic system. The deictic properties of the demonstratives can be described either in terms of a binary system with the opposition between ‘proximal’ and ‘non-proximal’ areas as viewed from the deictic centre, or in terms of a multiple system that is organised hierarchically and may be divided into primary and secondary systems, which together define fifteen spatial zones around the deictic centre. Beyond spatial proximity, the demonstratives may also encode a number of non-deictic features such as quality, quantity, dimension, preciseness of location, and visibility. This paper distinguishes between six morphosyntactic classes of demonstratives and shows how the different deictic and non-deictic features correlate with their pragmatic uses.